2022
DOI: 10.7759/cureus.28644
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Guided Patient Setup Versus Traditional Tattoo Markers for Radiation Therapy: Is Tattoo-Less Setup Feasible for Thorax, Abdomen and Pelvis Treatment?

Abstract: Purpose: In this study, patient setup accuracy was compared between surface guidance and tattoo markers for radiation therapy treatment sites of the thorax, abdomen and pelvis.Methods and materials: A total of 608 setups performed on 59 patients using both surface-guided and tattoo-based patient setups were analyzed. During treatment setup, patients were aligned to room lasers using their tattoos, and then the six-degree-of-freedom (6DOF) surface-guided offsets were calculated and recorded using AlignRT system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Several clinical studies have demonstrated the wide usage of OSMS in radiotherapy positioning and realtime monitoring of tumours in the head, neck, chest, abdomen, and breast [23,[27][28][29][30].Optical guidance has proven to provide a stable system for patient positioning and real-time position tracking. In 2004, Keall reported successful clinical treatment using continuous kV image intrafraction monitoring, achieving submillimeter treatment accuracy and precision [31].The application of orthogonal kV imaging and cone beam CT (CBCT) further enhances the positioning ability.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated the wide usage of OSMS in radiotherapy positioning and realtime monitoring of tumours in the head, neck, chest, abdomen, and breast [23,[27][28][29][30].Optical guidance has proven to provide a stable system for patient positioning and real-time position tracking. In 2004, Keall reported successful clinical treatment using continuous kV image intrafraction monitoring, achieving submillimeter treatment accuracy and precision [31].The application of orthogonal kV imaging and cone beam CT (CBCT) further enhances the positioning ability.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al. showed larger rotations (>3° in any yaw, roll or pitch direction) in 18.6% of surface-guided setups, with the majority observed for abdominal and pelvic targets, highlighting the importance of checking a patient’s entire body pose ( 7 ). Naidoo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Giantsoudi et al showed no difference in setup shifts or average treatment time per fraction in patients receiving tattooless regional nodal irradiation (RNI) with volumetric modulated arc therapy (VMAT) versus those receiving three-dimensional conformal RT RNI with VITs (6). Zhao et al showed larger rotations (>3°in any yaw, roll or pitch direction) in 18.6% of surface-guided setups, with the majority observed for abdominal and pelvic targets, highlighting the importance of checking a patient's entire body pose (7). Naidoo et al performed a systematic review of 13 studies evaluating the accuracy and reproducibility of patient setup with SGRT versus conventional tattoo-based methods and showed SGRT mean systematic errors in the 3 translational directions were reduced relative to tattoo setups alone, and mean rotational errors were equivalent, thereby concluding that SGRT could improve setup accuracy and efficiency (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations